Emprego da citotoxicidade basal in vitro na redução do número de animais em ensaios de avaliação da toxicidade oral aguda: a grandisina e seu metabólito majoritário como protótipos - VIEIRA, Marcelo de Sousa (2009)
The animal replacement in expirements has been very encouraged by government and other institutions. However, in drugs development the animal replacement is not yet a reality, like at oral acute systemic tests. The validation of in vitro protocols is necessary for data generation with reproducibility, repetability and accuracy. In this study was validated at the Laboratório de Farmacologia e Toxicologia Celular- Faculdade de Farmácia/Universidade Federal de Goiás the protocol already validated by three laboratories (two in the USA and one at United Kingdom) and coordinated by ICCVAM: In Vitro Cytotoxicity Methods for Estimating Starting Doses for Acute Systemic Toxicity Tests, using the neutral red uptake in BAL/c 3T3-A31 cell line. It was used the grandisine, a lignan, and its major metabolite taken by fungi biodegradation. Our research group has identified a potential anti-tumoral action of grandisine, data not yet published. After in house validation we estimated the LD50 of grandisin and 4-O-demethylgrandisin: 617.72 mg/kg and 429.95 mg/kg, respectively. Both were classified under the GSH category 4.